The Role of Social Media in Marketing Communication for Santet Segoro Pitu Film - Andriano, Stefanus (Institut Komunikasi dan Bisnis LSPR, 2025)
The advancement of internet-based communication technologies has significantly transformed the marketing communication landscape, particularly for businesses aiming to boost sales and profitability. In Indonesia, where internet connectivity has markedly increased, social media has emerged as a crucial tool for marketing efforts. This study investigates how Hitmaker Studios uses these platforms to promote the horror film